INVESTIGATING SCHOOL LIBRARIAN’S ROLE IN PROMOTING NEW MEDIA LITERACY IN INDONESIA - Bachtiar, Rifqi (Annual International Conferences on Language, Literature, and Media, 2023)
Considering the strategic position of school librarians as a part of the school literacy team, examining their roles in promoting students’ literacy skills becomes essential. This study investigated the school librarian’s roles in promoting new media literacy (NML), elaborating on their strategy, challenge, and the types of NML skills they taught. It employed a qualitative model as the research design and interpretivism as the research paradigm. Furthermore, it used a thematic analysis to analyse the data by implementing the American Association of School Librarians (AASL) and New Media Literacy (NML) theory as the theoretical frameworks. Moreover, this study employed semi-structured interviews to generate the data. The findings showed that the school librarians promoted NML directly and indirectly. They directly promoted NML by teaching literacy ambassadors NML materials and indirectly promoted it by collaborating with stakeholders inside and outside schools through workshops, seminars, and training. They collaborated with all school members inside the school, while outside schools, they worked collaboratively with journalists, universities, police, and local governments. Moreover, their challenges were their limited budget, complex budget mechanism, lack of attention, and unclear future careers. However, to cope with these constraints, they performed the five school librarian’s roles: as teachers, leaders, informant specialists, program administrators, and instructional partners. Finally, looking at the characteristics of literacy activities, the four NML skills, comprising functional consuming (FP), critical consuming (CC), functional prosuming (FP), and critical prosuming (CP), were performed.